There goes my hero again: sport scandal frequency and social identity driven response*. (2nd January 2018) - Kelly, Sarah J.; Weeks, Clinton S.; Chien, P. Monica
Abstract: With sport scandals reported frequently in the media, it is important to understand how associated stakeholders are affected. In the current work, we investigated the impact of off-field sport scandal on key stakeholders (the sport, implicated team, sponsor brand), and the roles played by team identification and scandal frequency. A 2 (fandom) × 3 (scandal frequency) between-subjects quasi-experiment examined responses to scandal news stories. Ingroup fan attitudes became less favorable toward all stakeholders following scandal, especially when it was described as repeat behavior. This differed to outgroup fan attitudes, which became less favorable toward the sport, but were generally negative and stable for other stakeholders, irrespective of scandal frequency. Respondents were willing to attribute responsibility to particular perpetrators rather than the team, and tended to endorse sponsorship continuation simultaneously with perpetrator removal/sanction. Findings have strategic implications for those involved in sponsorship, sport marketing, and sport management.